2010
DOI: 10.1002/pip.1048
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxy‐free monocrystalline silicon thin film: first steps beyond proof‐of‐concept solar cells

Abstract: The “Epifree” process involves the lift‐off of a high‐quality monocrystalline film formed by reorganization upon annealing of cylindrical macropore arrays in silicon, and can thus provide high‐quality silicon films without resorting to costly epitaxy. The challenge of this new process lies in etching controlled and regular pores in silicon in a cost‐efficient way, and in developing a process compatible with the difficulty of handling a micron‐thin material. Proof‐of‐concept cells have previously been achieved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
64
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 10 publications
(11 reference statements)
1
64
0
Order By: Relevance
“…Finally, the resist residues are removed by dissolution in acetone. For the solar cell fabrication, a mesa heterojunction-emitter cell structure is used [24].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the resist residues are removed by dissolution in acetone. For the solar cell fabrication, a mesa heterojunction-emitter cell structure is used [24].…”
mentioning
confidence: 99%
“…This "Epifree" (epitaxy-free) technique and its specific use in solar cells are described extensively in ref. [24].…”
mentioning
confidence: 99%
“…Several available methods for the transfer of perovskite films are the laser lift-off process, 2,3 ion cutting, 4 the use of water-soluble substrates, 5,6 and the epifree process. 7,8 In this letter, an approach for film transfer is demonstrated that makes use of seed layers of nanosheets on arbitrary sacrificial substrates. Nanosheets are essentially two-dimensional single crystals; they have a constant thickness of a few nanometers at most and their lateral size is mostly in the micrometer range, 9 while their oriented crystal structure enables them to direct epitaxial growth of thin films.…”
mentioning
confidence: 99%
“…Here, the nanophotonic ultra-thin monocrystalline-silicon solar cell efficiently combines a kerf-less thin film method [18], a higher-absorption self-assembled nanotexture with amorphous order [19], with a robust surface passivation [20] and an optimal nanotexture integration [21]. This allows the scaling of the silicon thickness (830 nm) down to the sunlight wavelength, while boosting the optical performance (Jsc, short-circuit current) both for light in-coupling and light trapping without degrading the electrical performance (Voc, opencircuit voltage and FF, fill factor).…”
mentioning
confidence: 99%
“…The front surface of the initially micron-thin solar cell is textured with rounded inverse nanopyramids, the 'nanocups', that self-assemble with short-range order and are the result of a carefully engineered trade-off between photon and charge-carrier collection [19,21] ( figure 1(a); see the methods section for the fabrication details of the kerf-less monocrystalline film [18] and the nanocups [19]). The nanocups are covered with standard hydrogenated amorphous-silicon (a-Si:H) serving as the passivating layer and heterojunction emitter.…”
mentioning
confidence: 99%